Water apple (Syzygium samarangense) cuttings growth in response to a plant growth regulator - Faridatul Mukminah; Yuliantina Azka (Indonesian Soil Science Society of South Sumatra in Collaboration With Soil Science Department, Sriwijaya University, 2025)
This study aims to determine the effect of various doses of plant growth regulator (PGR) Rootone-F on growth of water apple cuttings (Syzygium samarangense). The research was carried out at the Balai Pengembangan dan Produksi Benih Tanaman Pangan Hortikultura in the Province of South Sumatra from July 2022 to September 2022. The experimental method used a randomized block design (RBD) which consisted of 4 (four) treatments and 6 (six) replications. The treatments included P0 = (without PGR), P1 = (PGR 100 mg/l water), P2 = (PGR 200 mg/l water), P3 (PGR 300 mg/l water). Parameters observed were the percentage of growing cuttings, branch length, number of branches, root length and number of roots. The results showed that application of the plant growth regulator Rootone-F with dose of 200 mg/l water had the best effect on the percentage of growing cuttings, namely 55.00%, branch length 0.88 cm and root length 6.13 cm, while the treatment with dose 300 mg/l water had the best effect on the growth of the number of roots, namely 5.50.